Improving the efficiency of the construction market by reducing the information asymmetry - Shpakov, А. (Ways to Improve Construction Efficiency, 2019)
The article discusses perspective areas for improving the construction industry market mechanisms by reducing the asymmetry of information that construction market participants have. The author concludes that in order to improve the efficiency of the construction market, it is necessary to determine effective market signals for its individual segments and improve the institutional structure of the market by creating specific institutions whose function will be to reduce information asymmetry.